Biomimetic metal-organic frameworks as protective scaffolds for live-virus encapsulation and vaccine stabilization. (1st April 2022) - Singh, Ruhani; White, Jacinta F.; de Vries, Malisja; Beddome, Gary; Dai, Meiling; Bean, Andrew G.; Mulet, Xavier; Layton, Daniel; Doherty, Cara M.
Abstract: The invaluable health, economic and social impacts of vaccination are hard to exaggerate. The ability to stabilize vaccines is urgently required for their equitable distribution without the dependence on the 'cold-chain' logistics. Herein, for the first time we report biomimetic-mineralization of live-viral vaccines using metal-organic frameworks (MOFs) to enhance their storage stability from days to months. Applying ZIF-8 and aluminium fumarate (Alfum), the Newcastle Disease Virus (NDV) V4 strain and Influenza A WSN strain were encapsulated with remarkable retention of their viral titre. The ZIF-8@NDV, ZIF-8@WSN and Alfum@WSN composites were validated for live-virus recovery using a tissue culture infectious dose (TCID50 ) assay. With the objective of long-term stabilization, we developed a novel, trehalose (T) and skim milk (SM) stabilized, freeze-dried MOF@Vaccine composite, ZIF-8@NDV+T/SM. The thermal stability of this composite was investigated and compared with the control NDV and non-encapsulated, freeze-dried NDV+T/SM composite at 4 °C, RT, and 37 °C over a period of 12 weeks. We demonstrate the fragility of the control NDV vaccine which lost all viability at RT and 37°C by 12 and 4 weeks, respectively. Comparing the freeze-dried counterparts, the MOF encapsulated ZIF-8@NDV+T/SM demonstrated significant enhancement in stability of the NDV+T/SM composite especially at RT and 37 °C upto 12 weeks. Statement of significance: Vaccination is undoubtedly one of the most effective medical interventions, saving millions of lives each year. However, the requirement of 'cold-chain' logistics is a major impediment to widespread immunization. Live viral vaccines (LVVs) are widely used vaccine types with proven efficacy and low cost. Nonetheless, their complex composition increases their susceptability to thermal stress. Several LVV thermostabilization approaches have been investigated, including their complex engineering and the facile addition of stabilizers. Still, the lack of a universal approach urgently requires finding a stabilization technique especially when additives alone may not be sufficient. Herein, we demonstrate MOF biomimetic-mineralization technology to encapsulate LVVs developing an optimised composite which significantly preserves vaccines without refrigeration for extended periods of time. Graphical abstract: Image, graphical abstract